Targeted Therapy in Ovarian Cancer - Marcus Vetter; Alexandra Leary (healthbook TIMES. Oncology Hematology)
Ovarian cancer (OC) is associated with a dismal prognosis and lack of curative treatment. Increased understanding of OC biology has led to the development of several targeted therapies, including antiangiogenic agents and poly(ADP-ribose) polymerase (PARP) inhibitors. Cell cycle inhibitors and endocrine therapy such as selective estrogen receptor down regulators are currently under development. In this article, we provide an overview of the current and emerging targeted therapies in OC.